2010
DOI: 10.1007/jhep12(2010)029
|View full text |Cite
|
Sign up to set email alerts
|

Gauss-Bonnet holographic superconductors

Abstract: We study holographic superconductors in five dimensional EinsteinGauss-Bonnet gravity both numerically and analytically. We find the critical temperature of the superconductor decreases as backreaction is increased, although the effect of the Gauss-Bonnet coupling is more subtle: the critical temperature first decreases then increases as the coupling tends towards the Chern-Simons value in a backreaction dependent fashion. We compute the conductivity of the system, finding the energy gap, and show that the eff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
102
0
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(117 citation statements)
references
References 33 publications
7
102
0
4
Order By: Relevance
“…It was found that the critical exponent of the condensation in Gauss-Bonnet gravity is β = 1/2 which is consistent with mean-field theory and previous studies [17]. Other studies on the holographic superconductors in the framework of Gauss-Bonnet-AdS black holes were carried out in [18][19][20][21][22][23][24].…”
Section: Jhep04(2016)058supporting
confidence: 86%
“…It was found that the critical exponent of the condensation in Gauss-Bonnet gravity is β = 1/2 which is consistent with mean-field theory and previous studies [17]. Other studies on the holographic superconductors in the framework of Gauss-Bonnet-AdS black holes were carried out in [18][19][20][21][22][23][24].…”
Section: Jhep04(2016)058supporting
confidence: 86%
“…Condensation of a charged scalar field on planar Gauss-Bonnet black holes has been investigated in the context of holographic superconductors [45,46,47]. In [27] the condensation of an uncharged scalar field on a hyperbolic Gauss-Bonnet black hole was studied.…”
Section: Discussionmentioning
confidence: 99%
“…Noting that an ingoing wave boundary condition near the horizon is A x (r) ∼ f (r) − iωL 2 (d−1)r+ , and a general behavior for d = 5 in the asymptotic AdS region (r → ∞) [20] is…”
Section: Electrical Conductivitymentioning
confidence: 99%
“…The AdS/CFT duality is a powerful tool for investigating strongly coupled gauge theories, the application might offer new insight into the study of strongly interacting condensed matter systems where the perturbational methods are no longer available. Therefore, much attention has been given to the studies of the AdS/CFT duality to condensed matter physics and in particular to superconductivity recently [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. In these studies most of the holographically dual descriptions for a superconductor are based on a model that a simple Einstein-Maxwell theory coupled to a charged scalar.…”
Section: Introductionmentioning
confidence: 99%